Pengaruh Work Family Conflict, Stres Kerja dan Kompensasi Terhadap Kinerja Karyawan di PT Nusa Gas Pratiwi - Hermawan, Rafisha Nabila; Saputra, Beny Mahyudi; Murdiyanto, Edi (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of work-family conflict, job stress, and compensation on employee performance at PT Nusa Gas Pratiwi. A quantitative approach with a survey method was employed, and data were collected through questionnaires distributed to 35 permanent employees. The data were analyzed using multiple linear regression with SPSS software. The results indicate that work-family conflict, job stress, and compensation have a positive and significant effect on employee performance both partially and simultaneously. The coefficient of determination (R²) of 0.900 implies that these three variables explain 90% of employee performance variation, while 10% is influenced by other factors outside the model. These findings reinforce the Job Demand-Resource and Role Enrichment theories, suggesting that job stress and role conflict can become positive driving forces when balanced with fair compensation and organizational support. Therefore, maintaining equilibrium between psychological and economic factors is essential to enhance employee productivity and loyalty.